U.S. market concentration and import competition - Mary Amiti; Sebastian Heise (Federal Reserve Bank of New York, 2021)
A rapidly growing literature has shown that market concentration among domestic firms has increased in the United States over the last three decades. Using confidential census data for the manufacturing sector, we show that typical measures of concentration, once adjusted for sales by foreign exporters, actually stayed constant between 1992 and 2012. We reconcile these findings by linking part of the increase in domestic concentration to import competition. Although concentration among U.S.-based firms rose, the growth of foreign firms, mostly at the bottom of the sales distribution, counteracted this increase. We find that higher import competition caused a decline in the market shares of the top twenty U.S. firms.
Keywords: F14; F60; L11; 330; market concentration; markups; import competition; international trade